Relationship between Toddler Nutrition Status and Development of Toddler age 12-36 months - Mei Lia nindya zulis Windyarti; Poppy Fransisca Amelia; EsyaIriandica Al Ashfiha (Universitas Andalas, 2020)
National development is essentially human development as a whole which must start as early as possible, namely from the womb and during infancy. The growth and development of infants and toddlers take place through certain patterns. The first three years from birth are a period in which billions of Glial cells continue to grow to fertilize neurons. Little one's head, but for the fact that the first three years of little one's development are golden periods in the formation of his smart brain. Because the brain grows very rapidly and will reach 70-80% in the first 3 years of your child's life. Based on the nutritional status of children under five (weight/age) in Sragen regency in 2011 there were 84.03% normal nutrition, 1.89% undernutrition, and 0.01% poor nutrition Preliminary study conducted in Nglangak Kwangen village, Gemolong Sragen, namely there are 55 toddlers, there are 4 toddlers who experience developmental disorders. Speech and language disorders of 2 toddlers and 1 toddler with gross motor impairment are toddlers aged 12 months who cannot sit alone without assistance.